Pan-Canadian Survey of Radiation Oncology Professional Involvement in Global Oncology Initiatives in Low- and Middle-Income Countries - Matthew Beckett; Mustafa Al Balushi; Jessica Chan; Viktor Iakovenko; Michael Roumeliotis; Tim Hanna; Fleur Huang; Maroie Barkati; Danielle Rodin; Jean-Marc Bourque (JCO Global Oncology)
PURPOSECanadian radiation oncology professionals have a strong history of involvement in global oncology initiatives worldwide. This pan-Canadian survey-based study was conducted to determine the current level of engagement of Canadian radiation oncologists (ROs) and medical physicists (MPs) in global oncology initiatives and broaden the development of these activities.MATERIALS AND METHODSThis was a cross-sectional study. The survey was designed to characterize current levels of engagement of Canadian ROs and MPs in global oncology initiatives. The survey was open from March 2019 to April 2020. It was disseminated to all Canadian Association of Radiation Oncology and Canadian Organization of Medical Physicists members with two subsequent email reminders.RESULTSSurvey responses were received from 40 (93%) of the 43 Canadian cancer treatment centers that offer radiotherapy. At least one RO responded at 34 centers (79%) and one MP from 34 centers (79%) with some overlap. A response was received from a total of 93 participants, 47 ROs and 46 MPs. Of all survey participants, 58% reported some experience with global oncology. Nineteen percent of the participants surveyed were currently directly involved in short- or long-term projects, more than half of which have opportunity for additional staff involvement. The projects spanned 26 countries in South America, Africa, and Asia. Quality improvement and capacity building accounted for 27% and 20% of initiatives, respectively. The most common area of engagement was in direct treatment care, accounting for 56% of the projects.CONCLUSIONThis study demonstrates the landscape of involvement of Canadian ROs and MPs in global oncology initiatives. The study also highlights areas of opportunity for broadening international participation and collaboration as it relates to global oncology for Canadian radiation oncology professionals.